Histopathological and biochemical investigations of protective role of honey in rats with experimental aflatoxicosis. Issue 1 (December 2016) - Yaman, Turan; Yener, Zabit; Celik, Ismail
Abstract Background Natural honey (honey) is considered as a part of traditional medicine all over the world. It has both antimicrobial and antioxidant properties, useful in stimulation of wounds and burns healing and gastric ulcers treatment. The aim of this study, for the first time, was to investigate the antioxidant properties and protective role of honey against carcinogen chemical aflatoxin (AF) exposure in rats, which were evaluated by histopathological changes in liver and kidney, measuring level of serum marker enzymes [aspartate aminotransferase (AST), alanin aminotransferase (ALT), gamma glutamil transpeptidase (GGT)], antioxidant defense systems [Reduced glutathione (GSH), glutathione reductase (GR), superoxide dismutase (SOD), glutathione-S-transferase (GST) and catalase (CAT)], and lipid peroxidation content in liver, erythrocyte, brain, kidney, heart and lungs. Methods Eighteen healthy Sprague–Dawley rats were randomly allocated into three experimental groups: A (Control), B (AF-treated) and C (AF + honey-treated). While rats in group A were fed with a diet without AF, B, and C groups received 25 μg of AF/rat/day, where C group additionally received 1 mL/kg of honey by gavage for 90 days. Results At the end of the 90-day experimental period, we found that the honey supplementation decreased the lipid peroxidation and the levels of enzyme associated with liver damage, increased enzymatic and non-enzymatic antioxidants in the AF + honey-treated rats. Hepatoprotective and nephroprotective effects of honey is further substantiated by showing almost normal histological architecture in AF + honey-treated group, compared to degenerative changes in the liver and kidney of AF-treated rats. Additionally, honey supplementation ameliorated antioxidant defens systems and lipid peroxidation in content in other tissues of AF + honey treated rats. Conclusion The present study indicates that honey has a hepatoprotective and nephroprotective effect in rats with experimental aflatoxicosis due to its antioxidant activity.